HEGEMONY OF SOCIAL IRREGULARIT (CRITICAL DISCOURSE ANALYSIS OF PRESIDENT JOKO WIDODO'S SPEECH RELATED TO THE PROHIBITION OF HOUSES OF WORSHIP) - Rahman, Abdul; Ma’ruf, Amir; Sutrisno, Adi; Sakaria, Sakaria (Universitas Negeri Makassar, 2023)
This research aims to uncover the social irregularities behind President Joko Widodo's speech on 17/01/2023 entitled